Decoupling Surface Hardness and Bendability of Polymer Film via Hydrogen Bonding in Ultraviolet Light Curing Systems - Yao, Kaifeng (Langmuir : the ACS journal of surfaces and colloids, 2025)
Hard and bendable polymer films are critically important in a wide range of applications. It is generally accepted that for polymers, increased cross-linking density leads to enhanced hardness, but often at the expense of bendability. Here, by selecting different UV monomers, thermal post-treatment, and addition of LiCl, a series of polymer films with varied cross-linking densities and bonding architectures were prepared through rapid UV curing. Comparative analysis reveals that, unlike other cross-linking, the introduction of hydrogen bonding effectively enhances surface hardness without deteriorating bending properties in this system. Compared to trimethylolpropane triacrylate, pentaerythritol triacrylate has a hydroxyl group to form hydrogen bonds, exhibiting higher hardness but no decrease in bendability. Upon thermal treatment of 4-acryloylmorpholine, the hardness variation correlates with hydrogen bonding, while the bending radius remains unchanged. The introduction of LiCl leads to the formation of coordination bonds in the polymer, resulting in increased hardness but a reduced bending performance. Contrary to the general understanding, the hardness and bending properties of the polymers were decoupled by introducing hydrogen bonding. This work provides a theoretical basis for the development of advanced functional polymeric materials with an optimized mechanical performance